The impact of the perception of leisure on recreational and tourism spaces in an urban area - Meyer, Beata; Niezgoda, Agnieszka (Turyzm/Tourism, 2018)
The purpose of the present paper is to attempt to identify relations between the changing perception of leisure and the creation of tourism and recreational spaces in urban areas. The authors focus in particular on changes associated with the so-called ‘third wave’ (TOFFLER 2001), time compression (NIEZGODA 2017), and departure from synchronization. These considerations are illustrated by an analysis of the recreational activity of Szczecin residents and of tourists, and attempt identifying the relations between recreational space and tourism space. With the constant compression of leisure time, tourism activities become more similar to the leisure activities of residents, which means both types occur in the same environment. Urban recreational and tourism spaces overlap in a way that makes it impossible to separate them, but still allows the distinction of certain sub-spaces where either tourism or recreational behavior prevails.